Urbanization and Sustainability of Artisanal Fishing Activities in Gaya Island Village, Kota Kinabalu, Sabah - Jalihah Md Shah; Dzurizah Ibrahim (Prodi Sosiologi FISIP Universitas Teuku Umar, 2020)
Fishing activities are usually associated with rural based economic activities. However, studies in Gaya Island Village, Kota Kinabalu, Sabah found that fisheries also carried out by the urban community. Urbanization have created opportunities and dilemmas for fishermen in these villages. This ethnographic study is based on two objectives (i) to discuss the impact of urbanization on fishermen economic life; and (ii) to describe factors affecting the sustainability of fishing activities in urban areas. The study found that urbanization open opportunities to the involvement of non-fishery employment among the fishing households, increased education awareness, fishermen engaged in part-time jobs, urban wage-earner and fixed income as well as enjoying urban facilities. All of these provide income stability to the fishing household in Gaya Island Village but at the same time invokes the issue of uncertainties in fisheries economic activity through tourism development and conservation. The involvement of fishing households in the urban economy especially in the service sector has led to the questionable future of this activity. However, this study found that the nature of the fisheries sector is easy to access, government incentives and fishing skills are among the factors that can influence the sustainability of fisheries activities among the fishing community in Kota Kinabalu city.